Do obese patients have worse outcomes after direct lateral interbody fusion compared to non-obese patients?. (March 2016) - Adogwa, Owoicho; Farber, S. Harrison; Fatemi, Parastou; Desai, Rupen; Elsamadicy, Aladine; Cheng, Joseph; Bagley, Carlos; Gottfried, Oren; Isaacs, Robert E.
Abstract: Obese patients undergoing lumbar spinal fusion surgery are a challenge to the operating surgeon. Direct lateral interbody fusion (DLIF) has been performed for degenerative disease of the lumbar spine with good outcomes; nevertheless, how obese patients fare compared to non-obese patients after DLIF remains unknown. The primary aim of this study is to compare rates of postoperative complications and long-term outcomes between obese and non-obese patients undergoing DLIF. Sixty-three patients (obese: 29, non-obese: 34) undergoing index DLIF for degenerative disease of the spine between 2010 and 2012 at our institution were retrospectively enrolled. We analyzed data on demographics, postoperative complications, back and leg pain, and functional disability over 2 years. Patients completed the Oswestry Disability Index (ODI) and Visual Analog Scale (VAS) back and leg pain numerical rating scores before surgery, then at 12 and 24 months after surgery. Outcomes and complication rates were compared between the cohorts. The cohorts were similar at baseline. Postoperative complications rates were similar between obese and non-obese patients. There was no statistically significant difference in the incidence of durotomy (p = 0.91), anterior thigh numbness (p = 0.60), cerebrospinal fluid leak (p = 0.91), postoperative infection (p = 0.37), or bleeding requiring transfusion (p = 0.16). No patient experienced a nerve injury or psoas hematoma. Both cohorts had similar 2 year improvement in VAS for back pain, leg pain, and ODI. Our study demonstrates that obese and non-obese patients undergoing DLIF have similar complication profiles; hence, a patient's weight should not be a contraindication to DLIF.